Recurrent thoracic duct cyst of the left supraclavicular fossa: A retrospective study of 6 observational case series and literature review. Issue 50 (17th December 2021) - Planchette, Julie; Jaccard, Clara; Nigron, Audrey; Chadeyras, Jean-Baptiste; Le Guenno, Guillaume; Castagne, Benjamin; Jamilloux, Yvan; Resseguier, Anne-Sophie; Sève, Pascal
Abstract : Abstract: The transient occlusion of the terminal thoracic duct is a rare disease responsible for renitent supraclavicular cysts. The aim of this study was to describe the clinical characteristics, evolution, and treatment. A retrospective multicenter study and literature review was carried out. The literature search (PubMed) was conducted including data up to 31 December 2020 and PRISMA guidelines were respected. This study identified 6 observational cases between September 2010 and December 2020. The search results indicated a total of 24 articles of which 19 were excluded due to the lack of recurrent swelling or the unavailability of full texts (n = 5). Fourteen patients (8 from literature) mostly reported a noninflammatory, painless renitent mass in the supraclavicular fossa which appeared rapidly over a few hours and disappeared spontaneously over an average of 8 days (range: from about 2 hours to 10 days). Anamnesis indicated a high-fat intake during the preceding days in all cases and 7 from literature found in the Medline databases. Recurrences were noted in 10 patients. Thoracic duct imaging was performed in all cases to detect abnormalities or extrinsic compression as well as to eliminate differential diagnoses. A painless, fluctuating, noninflammatory, and recurrent swelling of the left supraclavicular fossa in patients evoking an intermittent obstruction of the terminal portion of the thoracic duct was identified. A low-fat diet was found as safe and effective treatment.